HUBUNGAN PERIODE WAKTU PENDAFTARAN DENGAN KEPATUHAN PEMBAYARAN IURAN JAMINAN KESEHATAN NASIONAL PESERTA PBPU POST PELAYANAN SECTIO CAESAREAN DI RSIA MUSLIMAT JOMBANG - Banun Sih Kasuryan; Henry Sudiyanto; Dwi Helynarti Syurandhari (MEDICA MAJAPAHIT, 2022)
The issue of reverse selection is widely discussed, especially in the case of pregnancy. Participants register when they need services and then no longer pay dues. Data released by BPJS Kesehatan in October 2019 stated that 43.2% of participants were in arrears after receiving services. This study aimed to see the relationship between the registration time period and compliance with the payment of the National Health Insurance (JKN) dues for PBPU participants post sectio caesarean service at RSIA Muslimat Jombang in 2019.The type of research used was a case control study with two groups of data, namely JKN-KIS participants who did not comply with dues as the case group and JKN-KIS participants who did comply as the control group. The technique used was total sampling with 491 PBPU participants who received SC services at RSIA Muslimat Jombang during 2019.The data obtained by 58.5% of participants registered when they were pregnant, then 57% continued to pay dues and 43% stopped paying fees after service. Meanwhile, 41.5% others registered before pregnancy and 64% paid regularly and 36% stopped paying after service.The results of the chi square test analysis showed that 0.165 was the alpha value used, namely 0.05. These results indicatd that there was no relationship between the time period of registration and compliance with the payment of JKN dues for PBPU post SC service participants at RSIA Muslimat Jombang in 2019.Seeing these results which stated that there was no relationship between the registration period and payment compliance, it is necessary to explore other factors that affect participant compliance in paying. It is necessary to take an attitude towards conditions of high adverse selection. It is necessary to build public awareness regarding the principle of mutual cooperation which is the principle of JKN-KIS.